2021
DOI: 10.1002/csc2.20449
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity and agronomic traits of durum wheat germplasm under drought environment of the northern Great Plains

Abstract: Durum wheat (Triticum turgidum L. ssp. durum) is an important food crop worldwide. Modern breeding has yielded elite durum wheat cultivars with improved grain yield, end‐use quality, and disease resistance. In this study, we compared 150 breeding lines from the North Dakota State University (NDSU) durum wheat breeding program to 163 durum landraces using a large set of single nucleotide polymorphism (SNP) markers. We found that the genetic diversity of the NDSU durum breeding population was decreased by ∼60% r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…To meet the food needs of all parts of the world, people have cultivated about 30,000 wheat varieties, but mainly hexaploid bread wheat (Triticum aestivum), which accounts for about 95% of the world's wheat production [3]. The implementation of modern wheat breeding programs has accelerated the selection and breeding of new wheat varieties [4]. While they have improved the efficiency of the wheat industry, these programs have also resulted in the frequent mixing of wheat varieties.…”
Section: Introductionmentioning
confidence: 99%
“…To meet the food needs of all parts of the world, people have cultivated about 30,000 wheat varieties, but mainly hexaploid bread wheat (Triticum aestivum), which accounts for about 95% of the world's wheat production [3]. The implementation of modern wheat breeding programs has accelerated the selection and breeding of new wheat varieties [4]. While they have improved the efficiency of the wheat industry, these programs have also resulted in the frequent mixing of wheat varieties.…”
Section: Introductionmentioning
confidence: 99%
“…The significant difference detected among the evaluated genotypes indicates sufficient variability and promising resources that could be utilized for breeding drought-tolerant genotypes. In this context, Nouri et al [39]; Mohammadi [40]; Salsman et al [41]; and Mohammadi et al [42] reported high genetic diversity for agronomic traits in durum wheat under drought stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Landraces are usually adapted to harsh environments, namely drought and heat conditions; thus, they are suited to low input agriculture. Comparisons between landraces and modern varieties indicate that, in most cases, yields of the current varieties are higher than that of landraces, because most comparisons are made in favorable environments and under intensive agricultural practices [103,104]. The idea is not to substitute the best-adapted local varieties for landraces but to use the best landraces as a source of desirable genes for better adaptation to abiotic stress.…”
Section: Abiotic Stressesmentioning
confidence: 99%
“…However, to make this breeding process a success, a large germplasm collection is required in order to locate suitable genes for drought tolerance for a particular target environment [100]. In some cases, such as yield under drought conditions, the interesting traits are not regulated by major genes but, rather, several QLTs with minor effects [104]. In those cases, finding genetic markers suitable for marker-assisted selection may present some practical challenges.…”
Section: Abiotic Stressesmentioning
confidence: 99%